2002
DOI: 10.1046/j.1537-2995.2002.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fetal D status from maternal plasma: introduction of a new noninvasive fetalRHDgenotyping service

Abstract: Combination of the sensitivity of real-time PCR with an improved RHD typing assay to distinguish RHD from RHDpsi enables highly accurate prediction of fetal D status from maternal plasma. This has resulted in the implementation of a clinical noninvasive fetal RHD genotyping service.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
262
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(277 citation statements)
references
References 27 publications
5
262
1
9
Order By: Relevance
“…The method has been used effectively to determine fetal sex, and since 2001 a molecular diagnostic service for fetal RHD genotyping has existed in the UK. 8,9,17 Testing for the prediction of C, c, E and Kell phenotypes has also been performed. [12][13][14][15] As early analysis during pregnancy allows timely and effective clinical treatment, we focused on women in early pregnancy (median 16 weeks of gestation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has been used effectively to determine fetal sex, and since 2001 a molecular diagnostic service for fetal RHD genotyping has existed in the UK. 8,9,17 Testing for the prediction of C, c, E and Kell phenotypes has also been performed. [12][13][14][15] As early analysis during pregnancy allows timely and effective clinical treatment, we focused on women in early pregnancy (median 16 weeks of gestation).…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Whereas numerous studies reporting data for several thousand pregnancies have demonstrated the accuracy of noninvasive prenatal diagnosis of the fetal D type, tests for C, c and E have been investigated in only a few studies with relatively small sample sizes, in which samples were mainly collected later in pregnancy. [12][13][14][15][16] DNA testing earlier in pregnancy has now been established for RhD determination.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, the placenta undergoes apoptosis and releases fragmented DNA that circulates as cell-free DNA (cfDNA) in the maternal plasma, together with the much larger amounts released from maternal cells. Early in pregnancy, small amounts of fetally derived cfDNA exist, but the fraction of fetal cfDNA in the maternal circulation increases with advancing gestational age (Finning et al 2002). Only a small amount of placentally derived template material in a large surplus of maternal cfDNA is available for PCR amplification.…”
Section: Fetal Blood Group Typingmentioning
confidence: 99%
“…Azokban az esetekben, ahol az anyai és magzati eredetű fragmentumok között különbség van, például fi ú magzat vagy RhD-negatív anya RhD-pozitív magzata, a plazmában keringő szabad DNS megbízhatóan használható nem invazív diagnosztikai céllal [15,16,17,18,19,20]. Az esetek más részében egy adott génre nézve az anyai és magzati, valamint apai allélok nem feltétlenül különbözőek.…”
Section: A Magzati Aneuploidiák Nem Invazív Vizsgálataunclassified